Nilai-Nilai Tafsir Tarbawi Surat Yusuf Ayat 2 Dalam Pembelajaran Bahasa Arab - Mirza, Iskandar; Taufiq, Ridwan (Penerbit Widina, Widina Media Utama, 2025)
The Qur'an was revealed in Arabic for easy understanding. Arabic has grammatical and semantic peculiarities so that the revelation is conveyed with beauty and depth of meaning. The learning of Arabic in madrasas faces obstacles that cannot achieve the main goal of understanding the divine message. The main purpose of learning Arabic in the Quran is found in Surah Yusuf verse 2. In reality, the madrasas have not linked the teaching materials with the context of the verse. As a result, Arabic language learning is separated from its main purpose of understanding the Qur'an. This research uses a qualitative approach with a literature review method. This approach aims to explore and understand the values of tarbawi tafsir in Arabic language learning. The main data will be obtained from relevant literature sources such as books of tafsir, hadith, academic books, scientific journals and works that discuss Islamic education, tafsir tarbawi and Arabic language learning. Arabic language learning integrated with the Quran will find religious, moral, scientific, social, aesthetic and practical values. The values of Islamic education in the verses of the Qur'an must be integrated into the learning of Arabic so that students are aware that they are able to absorb the educational values of the Qur'an while learning Arabic. It is necessary to formulate a plan that integrates the noble values of the Qur'an in learning Arabic. Find character values that can be integrated into the Arabic learning plan so that it can be implemented and evaluated.ABSTRAKAl-Qur’an diturunkan dalam bahasa Arab agar mudah difahami. Bahasa Arab mempunyai keistimewaan gramatikal dan semantik agar wahyu disampaikan dengan penuh keindahan dan kedalaman makna. Pembelajaran Bahasa arab di madrasah mengalami kendala tidak bisa sampai pada tujuan utama yaitu memahami pesan Ilahi. Tujuan utama pembelajaran Bahasa arab dalam Al-Quran terdapat di surat Yusuf ayat 2. Realita di lapangan, madrasah belum mengaitkan materi ajar dengan konteks ayat. Akibatnya, pembelajaran bahasa Arab terpisah dari tujuan utamanya, yaitu memahami Al-Qur'an. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka. Pendekatan ini bertujuan untuk menggali dan memahami nilai-nilai tafsir tarbawi dalam pembelajaran bahasa Arab. Data utama diperoleh dari sumber-sumber literatur yang relevan, seperti kitab tafsir, hadis, buku-buku akademik, jurnal ilmiah, dan karya-karya yang membahas pendidikan Islam, tafsir tarbawi, serta pembelajaran bahasa Arab. Pembelajaran Bahasa arab yang terintegrasi dengan Al-Quran akan menemukan nilai-nilai religius, akhlak, ilmiah, social, estetika dan praktis. Nilai-nilai Pendidikan islam yang ada dalam ayat-ayat Al-Quran harus diintegrasikan dalam pembelajaran Bahasa arab, sehingga para siswa sadar Ketika belajar Bahasa arab mereka mampu menginternalisasi nilai-nilai Pendidikan dalam Al-Quran. Perlu dirumuskan perencanaan yang mengintegrasikan nilai-nilai luhur yang pada Al-Quran dalam pembelajaran Bahasa arab. Ditemukan nilai-nilai karakter yang dapat diintegrasikan dalam perencanaan pembelajaran Bahasa arab hingga bisa di implementasikan dan dievaluasi.